HUBUNGAN PENGETAHUAN DAN PERILAKU CUCI TANGAN DENGAN KEJADIAN COVID-19 PADA REMAJA DI KELURAHAN DESA KAYU AGUNG TAHUN 2022 - Muhamad Zidan Alif; Yayah Choeriyah (Yayasan Nusantara Hasana Berdikari, 2023)
The covid-19 virus is increasing so much that the WHO has designated this virus as a pandemic. The most effective prevention of the spread of COVID-19 is to break the chain of transmission associated with the ways of transmitting COVID-19 by complying with health protocols. The Centers for Disease Control and Prevention (CDC), has set recommendations for prevention. One of them is by washing hands. Hand washing is one of the most important things in preventing transmission. This study was to determine the relationship between knowledge and hand washing behavior with the incidence of covid-19 in adolescents in Kayu Agung Village in 2022. This study using the google form. Population in this study were teenagers in the village of Kayu Agung totaling 84. Instrument of this study was a questionnaire. This study used the Chi-Square Test, with p-value 0.014 <0.05 for the relationship between knowledge and the incidence of covid-19 in adolescents and p-value 0.031 <0.05 for handwashing behavior with the incidence of covid-19 in adolescents. There is a relationship between knowledge and hand washing behavior with the incidence of Covid-19 in adolescents in Kayu Agung Village in 2022.